2021
DOI: 10.1021/acs.chemmater.1c00905
|View full text |Cite
|
Sign up to set email alerts
|

Database, Features, and Machine Learning Model to Identify Thermally Driven Metal–Insulator Transition Compounds

Abstract: Metal–insulator transition (MIT) compounds are materials that may exhibit metallic or insulating behavior, depending on the physical conditions, and are of immense fundamental interest owing to their potential applications in emerging microelectronics. An important subset of MIT materials are those with a transition driven by temperature. The number of thermally driven MIT materials, however, is scarce, which makes delineating these compounds from those that are exclusively insulating or metallic challenging. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Most MIT materials are transition metal oxides [7] and, as a model system in which to study MITs, the rare earth nickelates are a shining example for multiple reasons. These include -when synthesised as epitaxial thin films -their high quality and adaptability in terms of multilayer and superlattice structures as well as their intrinsic physics [8] .…”
Section: Metal-insulator Transitions In Rare-earth Nickelatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most MIT materials are transition metal oxides [7] and, as a model system in which to study MITs, the rare earth nickelates are a shining example for multiple reasons. These include -when synthesised as epitaxial thin films -their high quality and adaptability in terms of multilayer and superlattice structures as well as their intrinsic physics [8] .…”
Section: Metal-insulator Transitions In Rare-earth Nickelatesmentioning
confidence: 99%
“…Machine learningas a model-agnostic toolmay be used to remove some of these biases and provide new insight into yet unexplored directions. This may also help overcome some of the limitations inherent in current theoretical studies of MIT materials and may not need the same amount of user input as, for instance, a first principles calculation [7]. ML approaches, for example, using classifiers trained on existing literature [7,76] can be useful in quickly identifying which materials should be studied in more detail from large databases such as Materials Project [63].…”
Section: Materials Discovery Analysis and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Such configurations may be susceptible to metalinsulator transitions (MIT), which we assess using a recently devised machine-learning classification model [57]. We found that the binary MIT-non MIT classifier tends to predict most of the 2D halides are candidate MIT compounds, giving a positive MIT classification for CrCl 3 , FeCl 3 , IrBr 3 , MnCl 2 , RuCl 3 , TiCl 2 , VCl 3 and ZrI 2 , and a negative classification for CrI 3 , FeI 2 and NiI 2 .…”
Section: B Survey Of Broken Symmetry Phasesmentioning
confidence: 99%
“…Certain members of this family feature superconductivity, metal-to-insulator transitions and electric-field-induced resistive switching. [6][7][8] Most notably, the magnetic phase diagram of these compounds may host magnetic skyrmion phases. 4 Skyrmions are swirling spin structures, mostly found in chiral magnets.…”
Section: Introductionmentioning
confidence: 99%